Sequential Associations Between Caregiver Talk and Child Play in Autism Spectrum Disorder and Typical Development. Issue 3 (26th May 2017) - Bottema‐Beutel, Kristen; Malloy, Caitlin; Lloyd, Blair P.; Louick, Rebecca; Joffe‐Nelson, Linnea; Watson, Linda R.; Yoder, Paul J.
Abstract : This study examined sequential associations between child play and caregiver talk in 98 caregiver–child dyads ( M mental age = 14 months). Fifty dyads included a child with autism spectrum disorder (ASD). Analyses revealed sequential associations between child play and caregiver follow‐in (FI) utterances (utterances related to the child's attentional focus) were stronger in the ASD as compared to the typically developing (TD) group. FI utterances were more likely to elicit functional play than caregiver‐focused utterances, and more so in the ASD group. Across groups, FI directives were more likely to elicit functional play than FI comments. These findings have important implications for research involving caregiver–child play as an early intervention context for children with ASD.